Mortality of elder financial and psychological abuse victims in rural Malaysia: a prospective cohort study - Raudah Mohd Yunus; Farizah Hairi; Noran N Hairi; Wan Yuen Choo; Sajaratulnisah Othman; Rajini Sooryanarayana; Norliana Ismail; Sharifah Nor Ahmad; Inayah Abdul Razak; Devi Peramalah; Awang Bulgiba Awang Mahmud; Halima B Awang; et al. (BMJ Open)
Objectives To determine the longitudinal impact of elder financial and psychological abuse on risk of death among older Malaysians.Design 7-year prospective cohort study. Baseline data were collected in late 2013 and respondents were followed up in June 2020.Setting Kuala Pilah, Negeri Sembilan, Malaysia.Participants 1927 community-dwelling older adults aged 60 or older randomly sampled from the national census. Individuals with severe cognitive impairment were excluded.Outcome measure Mortality data were provided by the Malaysian National Registration Department and linked to respondents’ national identification numbers. Kaplan-Meier curves and Cox regression were used to examine victims’ survival periods and the impact of abuse on risk of death.Results Overall, 450 respondents (23.4%) died after 7 years. Among financial and psychological abuse victims, death percentage was 25.8% compared with 23.3% among those who did not experience these types of abuse. Kaplan-Meier curves showed shorter survival among abuse victims, but Cox regression found no significant impact of financial and psychological abuse on mortality risk (HR 1.05, 95% CI 0.78 to 1.41). Among all the variables studied, only cognitive impairment led to higher mortality risk (HR 1.32, 95% CI 1.03 to 1.69).Conclusion Our findings contradict prior empirical studies that supported the link between elder abuse and neglect (EAN) and mortality, even though we focused on two abuse subtypes. Results in this study are more in line with the recently emerging evidence that showed no association between EAN and mortality.